Exclusive Cultural Event Strategies for Advancing Sustainable Tourism in Bali - Ganang Aditiyo Prakoso; Yuliana Yuliana; Victor Bangun Mulia (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This research aims to analyze strategies for developing exclusive cultural events to support sustainable tourism in Bali by focusing on cultural preservation, community involvement, and quality visitor experiences rather than increasing tourist numbers alone. Method: This study uses a qualitative case study approach. Data were collected through in-depth interviews with five experts in event management and tourism. The data were then analyzed using the SWOT framework to identify strengths, weaknesses, opportunities, and threats related to the implementation of exclusive cultural events in Bali. Result: The findings show that Bali has strong advantages, such as authentic cultural heritage, a well-known destination image, and institutional support. Opportunities also come from the growing global demand for quality tourism and collaboration across sectors. However, challenges remain, including limited human resource capacity, lack of technological innovation, and the continued dominance of mass tourism trends. Contribution: This research contributes to event management and tourism studies by showing that curated, immersive, and community-based cultural events can become an effective strategy for sustainable tourism development. The findings can help policymakers, tourism stakeholders, and event organizers design tourism programs that protect culture, strengthen local communities, and improve destination sustainability.